4-Hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicides: past, present, and future. (21st February 2023) - Jhala, Amit J.; Kumar, Vipan; Yadav, Ramawatar; Jha, Prashant; Jugulam, Mithila; Williams, Martin M.; Hausman, Nicholas E.; Dayan, Franck E.; Burton, Paul M.; Dale, Richard P.; Norsworthy, Jason K.
Abstract: The herbicides that inhibit 4-hydroxyphenylpyruvate dioxygenase (HPPD) are primarily used for weed control in corn, barley, oat, rice, sorghum, sugarcane, and wheat production fields in the United States. The objectives of this review were to summarize 1) the history of HPPD-inhibitor herbicides and their use in the United States; 2) HPPD-inhibitor resistant weeds, their mechanism of resistance, and management; 3) interaction of HPPD-inhibitor herbicides with other herbicides; and 4) the future of HPPD-inhibitor-resistant crops. As of 2022, three broadleaf weeds (Palmer amaranth, waterhemp, and wild radish) have evolved resistance to the HPPD inhibitor. The predominance of metabolic resistance to HPPD inhibitor was found in aforementioned three weed species. Management of HPPD-inhibitor-resistant weeds can be accomplished using alternate herbicides such as glyphosate, glufosinate, 2, 4-D, or dicamba; however, metabolic resistance poses a serious challenge, because the weeds may be cross-resistant to other herbicide sites of action, leading to limited herbicide options. An HPPD-inhibitor herbicide is commonly applied with a photosystem II (PS II) inhibitor to increase efficacy and weed control spectrum. The synergism with an HPPD inhibitor arises from depletion of plastoquinones, which allows increased binding of a PS II inhibitor to the D1 protein. New HPPD inhibitors from the azole carboxamides class are in development and expected to be available in the near future. HPPD-inhibitor-resistant crops have been developed through overexpression of a resistant bacterial HPPD enzyme in plants and the overexpression of transgenes for HPPD and a microbial gene that enhances the production of the HPPD substrate. Isoxaflutole-resistant soybean is commercially available, and it is expected that soybean resistant to other HPPD inhibitor herbicides such as mesotrione, stacked with resistance to other herbicides, will be available in the near future.